Chihuahua-Sacramento and Tabalaopa-Aldama aquifers of Chihuahua state, Mexico: linkage and importance of geostatistical and hydrogeochemical analysis. Issue 3 (22nd December 2021) - Núñez, J.; Herrera, E.; Navarro, C. J.
Abstract: The objective of this study is to gather sufficient information to make a diagnosis of drinking water sufficiency in the Chihuahua-Sacramento and Tabalaopa-Aldama aquifers. By applying advanced statistical techniques, the goal is to find the variables that control the regional and intermediate flow systems and establish the characteristics of a heterogeneous aquifer. The variables chosen from those established were as follows: total solids (TS), nitrates (NO3 ), fluoride (F), and total hardness, among others. In order to establish a conceptual model, the results from all the sampling were carried out by the National Water Commission (CONAGUA) in the aforementioned aquifers and were used to obtain an approximate flow differentiation. The results showed a good flow differentiation. In addition, a group of mixed water was detected among the intermediate and regional flows. The increase in the average regional flow values suggests a rise in the incidence of an upward flow of the regional flow as a result of uncontrolled extraction. HIGHLIGHTS: Evaluate the relationships between the components of the local hydrological cycle, both surface and underground, to minimize existing conflicts in the use of water by users. The systemic approach that this work has, means that the way of approaching objects and phenomena cannot be isolated, but must be seen as part of a whole. A multivariate statistical model is used where the measurement response function plays a fundamental role, which must guarantee the number of underlying variables between wells and surface water bodies that are taken into account for comparison. It is hypothesized that the variations in the phreatic levels of the wells must be highly correlated with the oscillations of the variables that describe the bodies of water and the temperature of the underground flows with the fluorine contents. This will serve as a temporal and spatial guide to monitor the behavior of water quality and its temperature.